IMPLEMENTASI KEBIJAKAN SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU DI SMP NEGERI 4 DAN SMP NEGERI 5 PEKANBARU OLEH DINAS PENDIDIKAN PEKANBARU TAHUN 2019 - Dian Rahmadini; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The zoning system is one of the state's guidelines for new student admissions and is a zoning system. The implementation of the zoning system has been carried out in stages since 2016, starting with the use of zoning for the administration of national exams. The zoning system was first introduced at PPDB in 2017 and refined in 2018. This system has a positive effect by making it easier for prospective students to study close to where they live. However, in its implementation there are still obstacles. This problem is inseparable from the lack of public knowledge and information about PPDB zoning. This research is qualitative and collects data in the form of interviews and document research. The purpose of this study was to find out how the Pekanbaru City Education Office implemented a zoning system policy on PPDB at SMPN 4 and SMP N 5 Pekanbaru in 2019. The results show that this is. The zoning policy for SMPN 4 and SMPN 5 Pekanbaru, Pekanbaru is still not optimal. This is reflected in the lack of public understanding of the zoning system, and the lack of socialization during PPDB. This results in a lack of zoning information in the PPDB for the community. Keywords : Zoning System, Policy, Implementation, PPDB